192 Building inclusive research: A training program for CRP students and staff on equitable participant engagement, recruitment, and retention - Jessica Cranfill; Stephanie A. Freel; Christine E. Deeter; Denise C. Snyder; Susanna Naggie; Nadine Barrett; Jamie N. Roberts (Journal of Clinical and Translational Science)
Objectives/Goals: Clinical trial success requires recruiting and retaining diverse participants. The ER&R Certificate Program trains clinical research professionals (CRPs) in equity, diversity, and inclusion (EDI), addressing biases, and integrating regulatory knowledge with practical skills to foster inclusive research practices. Methods/Study Population: An interdisciplinary Steering Committee, supported by Duke CTSI and DOCR, developed and implemented an engagement, recruitment, and retention certificate program (ER&R) for CRPs. With expert-led instruction, including e-learning, group sessions, and hands-on activities, ER&R integrates EDI into participant engagement practices. Participants complete 7 core courses and at least 3 elective courses, reflecting their unique responsibilities. Program evaluation uses the Kirkpatrick model to assess participant learning, competency, and EDI integration into clinical research. Since launch, the program has expanded to include clinical research trainees from Durham Technical Community College. All elements of the program were designed to allow for sharing across academic medical institutions. Results/Anticipated Results: A total of 202 CRPs and trainees have participated since launch (2020), including 17 trainee participants from Durham Technical Community College (2022–2024). Post-program evaluations showed significant growth in recruitment and retention self-efficacy. An early evaluation of the first 2 cohorts (n = 59) included a self-assessment across defined competencies showing marked increases in comfort across all learning objectives, with notable gains in: Community and Stakeholder Engagement, Recruitment on a Shoestring Budget, Community-Engaged Research Initiatives, and Social Marketing. Participants valued the program’s focus on EDI and sought more practical strategies and peer collaboration. 50 additional institutions have engaged with our implementation consultations and program repository. Discussion/Significance of Impact: Barriers to equitable ER&R exist at the individual, study, and system levels. Addressing these requires more intentional engagement practices. The ER&R certificate program is an innovative model for integrating equity principles with practical and required knowledge and skills training for participant-facing research professionals.